A Comparative Overview of PI and Fuzzy Logic Based IPFC on Damping of Power System Oscillations - S. N. Dhurvey; V. K. Chandrakar; P. P. Ashtankar (Techniques and Innovation in Engineering Research Vol. 1, 2022)
This research introduces a novel fuzzy logic-based Interline Power Flow Controller (IPFC) approach for identifying the appropriate control signals for oscillation damping. The IPFC perfor- mance is tested with PI controllers in comparison with fuzzy logic based controller on Modified Phllips-Heffron Model of Single Machine Infinite Bus System to achieve improved damping per- formance by selecting effective control signals such as deviation in pulse width modulation index of voltage series converter 1 in line 1, pulse width modulation index of voltage series converter 2 in line 2, deviation in phase angle of the injected voltage of convertor 1, injected voltage phase an- gle deviation of convertor 2. Investigations have shown that the resilient dynamic performance is produced by the coordinated tuning of an interline power flow controller and fuzzy logic controller. Simple fuzzy rules are used in the Fuzzy Logic Based Interline Power Flow Controller [IPFC] design to coordinate the additional damping signal. The proposed controllers for IPFC are capable of improving the power system’s designed performance. By using eigen value analysis, the validity of effective control signals has been determined.